Infrared electrochromic conducting polymer devices. Issue 23 (30th May 2017) - Brooke, Robert; Mitraka, Evangelia; Sardar, Samim; Sandberg, Mats; Sawatdee, Anurak; Berggren, Magnus; Crispin, Xavier; Jonsson, Magnus P.
Abstract : Metal-free, flexible infrared electrochromic devices were fabricated using PEDOT:Tos as both the electrochromic and the electrode material, enabling modulation of the devices' infrared signature and their effective temperature as seen by a thermal camera. In addition to evaluating the practical suitability of these devices, we report a detailed investigation of the thin film spectroscopic properties. Abstract : The conducting polymer poly(3, 4-ethylenedioxythiophene) (PEDOT) is well known for its electrochromic properties in the visible region. Less focus has been devoted to the infrared (IR) wavelength range, although tunable IR properties could enable a wide range of novel applications. As an example, modern day vehicles have thermal cameras to identify pedestrians and animals in total darkness, but road and speed signs cannot be easily visualized by these imaging systems. IR electrochromism could enable a new generation of dynamic road signs that are compatible with thermal imaging, while simultaneously providing contrast also in the visible region. Here, we present the first metal-free flexible IR electrochromic devices, based on PEDOT:Tosylate as both the electrochromic material and electrodes. Lateral electrochromic devices enabled a detailed investigation of the IR electrochromism of thin PEDOT:Tosylate films, revealing large changes in their thermal signature, with effective temperature changes up to 10 °C between the oxidized (1.5 V) and reduced (−1.5 V) states of the polymer. Larger scale (7 × 7 cm) vertical electrochromic devices demonstrate practical suitability and showed effective temperature changes of approximately 7 °C, with good optical memory and fast switching (1.9 s from the oxidized state to the reduced state and 3.3 s for the reversed switching). The results are highly encouraging for using PEDOT:Tosylate for IR electrochromic applications.